2015
DOI: 10.1016/j.mrfmmm.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence context greatly affects the accuracy of bypass across an ultraviolet light 6-4 photoproduct in mammalian cells

Abstract: Translesion DNA synthesis (TLS) is a DNA damage tolerance mechanism carried out by low-fidelity DNA polymerases that bypass DNA lesions, which overcomes replication stalling. Despite the miscoding nature of most common DNA lesions, several of them are bypassed in mammalian cells in a relatively accurate manner, which plays a key role maintaining a low mutation load. Whereas it is generally agreed that TLS across the major UV and sunlight induced DNA lesion, the cyclobutane pyrimidine dimer (CPD), is accurate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Furthermore, UV irradiation elicits monoubiquitination of PCNA by Rad6/Rad18 and phosphorylation of pol η, both of which are imperative for pol η-mediated TLS in vivo 34, 198 . However, Polη has an eightfold preference for mis-insertion at (6–4)PPs and pols ζ, ι, and κ all perform mutagenic TLS across CPDs in human cells lacking functional pol η 58, 65, 67, 68 . Thus, DNA-damaging agents and the cellular response they trigger may generically target TLS pols to damaged DNA but selection of the appropriate TLS pol(s) and, hence, the fidelity of DNA damage bypass is ultimately governed by the DNA lesion itself and perhaps the surrounding sequence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, UV irradiation elicits monoubiquitination of PCNA by Rad6/Rad18 and phosphorylation of pol η, both of which are imperative for pol η-mediated TLS in vivo 34, 198 . However, Polη has an eightfold preference for mis-insertion at (6–4)PPs and pols ζ, ι, and κ all perform mutagenic TLS across CPDs in human cells lacking functional pol η 58, 65, 67, 68 . Thus, DNA-damaging agents and the cellular response they trigger may generically target TLS pols to damaged DNA but selection of the appropriate TLS pol(s) and, hence, the fidelity of DNA damage bypass is ultimately governed by the DNA lesion itself and perhaps the surrounding sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the vast majority of (6–4) PPs are repaired prior to an encounter with a moving replisome while most CPD lesions persist into and throughout S-phase. However, both lesions can be accommodated, i.e., “tolerated,” during S-phase by TLS and this process absolutely requires the interaction of TLS pols with PCNA encircling the damaged DNA 5864 .…”
Section: Escaping Detection: Uv-induced Dna Lesions In S-phasementioning
confidence: 99%
See 2 more Smart Citations
“…This result suggests that the fidelity of TLS can also contribute to the sequence preference for mutation induction as well as the ease of adduct formation and the resistance to nucleotide excision repair. Another study has also reported that sequence contexts contribute to the efficiency and coding property of TLS across a T-T (6–4) photoproduct (60). The mechanism by which neighboring bases influence the property of TLS remains to be determined…”
Section: Discussionmentioning
confidence: 99%